Ultrasonography versus computed tomography for initial investigation of suspected nephrolithiasis. Issue 4 (22nd January 2016) - Lin, Katie; Dowling, Shawn
Abstract : Clinical question: Is ultrasonography a safe and practical alternative to computed tomography for the initial investigation of suspected nephrolithiasis? Article chosen: Smith-Bindman R, Aubin C, Bailitz J, et al. Ultrasonography versus computed tomography for suspected nephrolithiasis. N Engl J Med 2014;371(12):1100-10. Objective: To assess the safety and efficacy of ultrasonography as a first-line imaging investigation for patients with suspected nephrolithiasis.